PENGARUH CELEBRITY ENDORSER DAN PESAN IKLAN TERHADAP KEPUTUSAN PEMBELIAN ICE CREAM WALLS CORNETTO DISC CHOCOLATE DI KOTA BOGOR - Abdul Zaelani; Lucky Hikmat Maulana (Fakultas Ekonomi Universitas Djuanda, 2017)
The purpose of the research is to determine effect celebrity endorser and advertising messages to purchase decision ice cream walls cornetto disc chocolate in Bogor City. Questioner distributed 100 konsuments. The method used is descriptive analysis and verification. The questioner validity and reliability testing. Likert scale used prior to testing with multiple regressions. In order to know the effect of four free variable that is used for dependent variable.Based on the result all indicators expressed validity and reliability, simultaneously with celebrity endorser (X1) and advertising messages (X2) influencing the purchase decision ice cream walls cornetto disc chocolate in Bogor City (Y). Partially, celebrity endorser and advertising messages influencing positive to purchase decision ice cream walls cornetto disc chocolate in Bogor City.Keywords: Celebrity Endorser, advertising messages and purchase decision